Analisis Standar Kompetensi Lulusan Madrasah Ibtidaiyah Kurikulum 2013 dalam Perspektif Surah Luqman Ayat 12-19 - Nida Dzu Suraiyah (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2017)
2013 Curriculum use three important aspects of education: cognitive, psychomotoric, and affective where more emphasis on character education in the standard of graduates of the realm of attitudes, knowledge and skills. From the three domains are closely related to the Surah Luqman verse 12-19, which contains advices to his son and suitable when applied to the character of the students present. This study aimed to analyze:(1)Standard Competency 2013 Curriculum, (2)Tafseer Surah Luqman verse 12-19. This study used a qualitative approach descriptive for the developmental research library research, the method used was thematic, while data analysis using content analysis. The results of this study found some domains listed in SKL K-13 that is the realm of attitudes, knowledge and skills, which are contained in a tafsir Luqman education in verse 12-19: First, Luqman gives his taught to always be grateful for everything that exists for him. Secondly, Luqman taught his son to Tawheed that is faithful to Allah. Third, Luqman taught his son to devote to his parents. Fourth, Luqman taught his son to prayers. Fifth, Luqman gives direction to his son to always preach in the way of Allah. Sixth, Luqman taught his son to behave in manners, not arrogant, and modest in walking and talking.